Justice for jumping - Part 3 - Haw, D. (The Professional Skater PS Magazine, 2020)
When it comes to the "Justice for Jumping" one must have a systematic approach to jumping. That means having a fixed plan or method that is almost fail proof. To me, the three greatest factors that affect jumping are pattern, positions and timing/rhythm! When a jump is executed first check the pattern….is it proportional to the skater`s height, weight, strength and talent to produce the best jump. When learning a jump, all patterns are smaller as you are skating slower to increase edge pressure. Are the positions on the pattern, preparation edge, take-off edge, flight and landing correct? Does the skater have the correct rhythm/timing of the steps, turns and knee action to compliment the pattern and positions? All of these factors are combined to coordinate with the seven biomechanical principles that produce all the forces and leans involved with jumping.